Use of methylene blue to investigate the adsorptive capacity of biomass (Research, Society and Development, 2021)
The present work aims to evaluate the adsorption capacity of biomass, orange bagasse (Citrus Sinensis), Pinus elliotti and Mezilaurus itaúba sawdust and eggshells against methylene blue dye, in addition to evaluating the assembly of the column packing, and after that, check if the desorption process was possible to be carried out. For this, the adsorption studies were carried out in a fixed bed column using orange bagasse, pinus elliotti sawdust, mezilaurus itaúba sawdust and eggshells as adsorbent. It was observed that using eggshells as an adsorbent, adsorption was slow (0.02 mL min-1), and the adsorption process did not occur, as for the other biomasses the adsorption process took place, and the biomass that presented best value was the orange bagasse, with a maximum adsorption capacity of 63 mg g-1, and the sawdust pinus elliotti and itaúba presented 29.0 and 15.6 mg g-1, respectively. The desorption process was feasible when using both sawdust as adsorbent, but using orange pomace it was not observed, as the desorption process became extremely slow, about 5 mL h-1, making it impossible to study of this parameter. Thus, it was possible to conclude that the best tested biomass was orange bagasse, that is, which has the highest adsorption capacity for the methylene blue dye.